The definition of graft and corruption and the conflict of ethics and law - Cariño, Ledivina V. (1979)
Philippine law follows the public-office definition of graft and corruption and includes those acts that are clearly private-regarding as well as those which may only appear to be so. The bureaucratic-legal norms are in marked contrast with personalism which the culture demands. The incongruence between legal and cultural standards is such that what are deemed unacceptable by law fall within the ideal and acceptable behavior according to the culture, and vice-versa. Nevertheless, the persistence of graft and corruption in Philippine
society does not necessarily manifest a legal-cultural conflict since the most problematic form of corruption involves cash payments, which are both not legally and culturally acceptable.
Keywords: Corruption; Corruption and ethics; Corruption -- Government policy; Corruption laws